Development of Ulos Designs and Motifs Using Traditional Weaving Tools - Siahaan, Septony; Napitupulu, Junika; Simanjuntak, Wesly Andri; Pasaribu, Dompak; Rajagukguk, Tiur; Panggabean, Toman; Mesakh, Januardi; Ijonris, Yusuf (PT FORMOSA CENDEKIA GLOBAL, 2024)
Ulos is a type of traditional textile with its own designs and motifs. In Dairi Regency there are areas of ulos cloth craftsmen, one of which is Silalahi Village 1. The ulos weaving craftsmen in Silalahi 1 Village admit that one of the basic problems experienced by the group of ulos weaving craftsmen is related to the design, motif and color/pattern of the weaving. generated. The implementation approach includes the socialization and dissemination stage, training stage and partner business mentoring stage which is carried out in stages to overcome partner problems. Training on designs, motifs and forms of ulos weaving begins with providing material about the nature of woven motifs, types of motifs and motif development according to market needs. Before weaving, weaving begins with a 'kneading' process, where the threads are arranged parallel to the width of the weave. Industrial design, on the other hand, includes not only industrial products but also craft patterns, including handicrafts. Therefore, the field of design includes various fields such as product design, textiles, interiors, graphics, architecture, engineering design, and urban design, which are created to meet human spiritual and material needs